MENINGKATKAN PRODUKSI BAWANG MERAH LEMBAH PALU(Allium wakegi Araki) DENGAN INOVASI TEKNOLOGI WAKTU PENGGEMBURAN TANAH DAN PUPUK ORGANIK CAIR - Trisutiyo, Trisutiyo; Maemunah, Maemunah; Jeki, Jeki (Fakultas Pertanian, Universitas Tadulako, 2023)
The objective of this research was to find the optimal combination of soil loosening timing and liquid organic fertilizer dosage to enhance the yield of Lembah Palu shallot variety. The study was conducted in Kayumalue Ngapa village, Central Sulawesi, from November 2019 to January 2020. A two-factorial randomized block design was employed. The first factor was the soil loosening time: loosening at 1, 3, 5 weeks after planting and loosening at 2, 4, 6 weeks after planting. The second factor was the application of liquid organic fertilizer: 150 ml/ha, 300 ml/ha, and 450 ml/ha. The findings revealed that the interaction between soil loosening time and liquid organic fertilizer dosage significantly affected the plant height parameter. Particularly, loosening the soil at 1, 3, 5 weeks after planting along with a 150 ml/ha dose of liquid organic fertilizer produced higher plant height. Moreover, the soil loosening time of 1, 3, 5 weeks after planting resulted in improved plant height, tuber diameter, and fresh tuber weight. Similarly, the liquid organic fertilizer of 150 ml/ha demonstrated positive effects on plant height.